Case Report: Conventional therapy versus volanesorsen in two sisters with familial chylomicronemia syndrome - Vega, Javier; Torres, Benjamín; Maiz, Alberto; Santos, José L. (Frontiers in Nutrition, 2026)
Familial chylomicronemia syndrome (FCS) is a rare autosomal recessive disorder characterized by severe hypertriglyceridemia and caused by mutations in genes involved in chylomicron metabolism. Dietary management includes a very-low-fat diet, restriction of simple carbohydrates and alcohol, supplementation with medium-chain triglycerides, essential fatty acids, and fat-soluble vitamins; however, long-term adherence is often poor and nutritional therapy alone is insufficient. We report two adult Chilean sisters with FCS caused by the homozygous Q97X mutation in the APOA5 gene. Both patients experienced severe hypertriglyceridemia (>5,000 mg/dL) and recurrent episodes of acute pancreatitis. One sister was treated with volanesorsen, an antisense oligonucleotide, receiving a weekly dose of 285 mg, which was repeated every 3 weeks due to thrombocytopenia. When combined with structured nutritional counseling, pharmacological treatment achieved a marked reduction in plasma triglycerides to <250 mg/dL and a substantial improvement in quality of life. The other sister was managed with conventional therapy due to a lack of health insurance coverage for volanesorsen. She presented persistent hypertriglyceridemia and recurrent hospitalizations, underscoring the challenges of access to advanced therapies in limited-resource settings. While volanesorsen offers a promising therapeutic alternative, equitable access remains a critical issue, particularly in health systems of low-to middle-income regions.